DEVELOPMENT OF SPEECH OF STUDENTS IN PRIMARY CLASSES WAYS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the concept of speech, the methodology of speech development, its importance, ways of developing students' speech, methodology, a number of aspects of speech acquisition, directions of speech development, clearly defined requirements for the development of students' speech, it is about life skills that should be formed in students by achieving speech development in the educational process.